The Transformation of Islamic Education Thought in the City of Padangsidimpuan: Abid al-Jabiri's Epistemological Study on the Role of Intellectuals and Educational Institutions - Asnah, Asnah (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
This research departs from concerns about the stagnation of Islamic educational thinking in Padangsidimpuan City, where textual, authoritative, and repetitive bayani reasoning models still dominate. In the midst of increasingly complex social dynamics and the demands of the times, local Islamic education often exhibits resistance to rational and critical approaches, thereby becoming entrenched in epistemological conservatism. Using a qualitative-critical approach and the analytical lens of Islamic epistemology, Abid al-Jabiri, this study examines in depth how the role of Islamic intellectuals and educational institutions in Padangsidimpuan not only reproduces traditions but also structurally hinders the emergence of a renewal paradigm. The results of the study show that bayani reasoning still dominates in the curriculum structure, institutional orientation, and local intellectual mindset. Meanwhile, transformation efforts through rational, contextual, and dialogical approaches are still partial and have not yet become mainstream in the discourse of Islamic education. This research recommends a bold and systemic epistemological reorientation by empowering local intellectuals as agents of thought reconstruction, as well as reorganizing educational curricula and institutional practices based on the integration of bayani, burhani, and ‘irfani reason. Thus, Islamic education in Padangsidimpuan can move out of intellectual stagnation towards an authentic, progressive, and reality-rooted transformation.